PERSEPSI MASYARAKAT TERHADAP MANTAN NARAPIDANA DI DESA BENUA JINGAH KECAMATAN BARABAI KABUPATEN HULU SUNGAI TENGAH - Muhammad Najibuddin (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2014)
Muhammad Najibuddin, 2013.”Public Perception of the Former Prisoners In Jingah Continent Village District of Barabai , Kabupaten Hulu Sungai middle (Study of Socio Cultural) ”. Skripsi Program Study of Citizenship and Pancasila Education, Department of Sosial Sciences Education, Faculty of Teacher and Education Science, University of Lambung Mangkurat. Counselor (I) Drs. Zainul Akhyar, MH (II) Drs. Harfani Matnuh M, MH.The phenomenon of today's society, that people still adhere to the norms of decency in society therefore they are of the view that ex-convict was still a disease of society after being released from house arrest, Similarly is the case today in the village of Continent Jingah. This study aims to find out the views of the public Continental Village Jingah to ex-convict, know the forms of discrimination against former prisoners, determine the factors that led to the former prisoners are discriminated against and to know the response of former inmates and their families against discrimination from society.The method used in this research is qualitative methods. Sources of data selected by purposive sampling. Data was collected through observation techniques, interview, and documentation. Analysis of the research results is the analysis of the reduction steps data, data display dan verification. Based on the results of research in village Benua Jingah Subdistrict Barabai District Hulu Sungai tengah Province South Kalimantan, the results showed that (1) view of society in village Benua Jingah against ex-convict, people think of them as social problems which is contrary to the public, because people who've imprisoned considered a bad person and violate the norms of decency. (2) forms of discrimination against former prisoners is compounded discrimination in matters of making ID cards, not been included in the activities of the Youth dan in terms of finding a job. (3) factors that led to the former prisoners are treated discriminatory because behavior shown ”eks” narapidana This after getting out of prison does not change, such as drug,gambling,anarchist, spoke disrespectful and rude. (4) response ex-convict and their families against discrimination from society, they keep coming back to the community to get together again with family, and they still want to try to be a person who could be accepted in society. The family of former inmates could also just put up with the treatment of their children. Based on the results of this study, can be suggested that the ex-convict who has been out of custody so be nice, polite and not do anything they have done in the past in order to be accepted by the community well, need the cooperation of the government ,society and of the ex-inmates in an attempt to build confidence and convince them not to be shunned in societyKeywords: Elapsed Understanding Cross, Student.